The Relationship Between Confirmed COVID-19 Positive Characteristics of Laboring Mothers and the Incidence of Asphyxia in Infants at Hospital Dr. Hasan Sadikin Bandung - Dinna Triyani; Akhmad Yogi Pramatirta; Sefita Aryuti Nirmala; Ari Indra Susanti; Astuti Dyah Bestari (Jurnal Ilmiah Kesehatan)
The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is the cause of